Low level laser therapy associated with a strength training program on muscle performance in elderly women: a randomized double blind control study. Issue 6 (August 2016) - Toma, Renata; Vassão, Patrícia; Assis, Livia; Antunes, Hanna; Renno, Ana
Abstract The aging process leads to a gradual loss of muscle mass and muscle performance, leading to a higher functional dependence. Within this context, many studies have demonstrated the benefits of a combination of physical exercise and low level laser therapy (LLLT) as an intervention that enhances muscle performance in young people and athletes. The aim of this study was to evaluate the effects of combination of LLLT and strength training on muscle performance in elderly women. For this, a hundred elderly women were screened, and 48 met all inclusion criteria to participate in this double-blind placebo-controlled trial. Volunteers were divided in three groups: control (CG = 15), strength training associated with placebo LLLT (TG = 17), and strength training associated with active LLLT (808 nm, 100 mW, 7 J) (TLG = 16). The strength training consisted of knee flexion-extension performed with 80 % of 1-repetition maximum (1-RM) during 8 weeks. Several outcomes related to muscle performance were analyzed through the 6-min walk test (6-MWT), isokinetic dynamometry, surface electromyography (SEMG), lactate concentration, and 1-RM. The results revealed that a higher work (p = 0.0162), peak torque (p = 0.0309), and power (p = 0.0223) were observed in TLG compared to CG. Furthermore, both trained groups increased the 1-RM load (TG vs CG:p = 0.0067 and TLG vs CG:p < 0.0001) and decreased the lactate concentration in the third minute after isokinetic protocol (CG vs TLG:p = 0.0289 and CG vs TG:p = 0.0085). No difference in 6-MWT and in fatigue levels were observed among the groups. The present findings suggested that LLLT in combination with strength training was able to improve muscle performance in elderly people.